Measurement of the electrical potential gradient in the atmosphere by radiosonde - VENKITESHWARAN, S.P.; GUPTA , B.K.; HUDDAR, B.B. (MAUSAM, 1954)
In a recent paper Venkiteshwaran, Dhar and Huddar (1953) have described a method to measure the electrical potential gradient in the atmosphere by radiosondes. They have adapted the valve electrometer of Koenigsfeld and Piraux (1951.) with the audio frequency modulated type of radiosonde used in the U.S.A. The HL 23 valve which works as an electrometer is coupled to the modulator circuit of the American radiosonde transmitter by disconnecting its temperature and humidity elements and replacing them with a wire wound resistance of about 350 ohms. This resistance formed the load between the grid and the cathode of the valve electrometer. A small potential of 6 volts is applied between the grid and the cathode of the HL23. The terminals from the collectors at known distances are connected to the plate and the cathode of this valve. The variations in the atmospheric potential gradient cause a corresponding change in the voltage across the load resistance which in turn alters the audio frequency of the modulator circuit of the radiosonde which is recorded on the ground equipment.